STUDYING INCIDENCE OF OBESITY AND DEMOGRAPHIC FACTORS RELATED TO IT IN 30 TO 60-YEAR-OLD WIVES OF STAFF WHO ARE WORKING IN OIL COMPANY OF SHIRAZ - HOJAT, FATEMEH; POURSAMAD, ABDOLLAH; POURMAHMOUDI, AZIZOLLA (International Journal of Clinical and Biomedical Research, 2016)
Introduction: obesity is one of health problems and risk factor for manifestation of other illnesses. The prevalence of this complication is increasing in many industrial countries specially America and developing nations. The present research aims to study prevalence of obesity and demographic factors related to it in 30 to 60-yearold wives of husbands who are working in Oil Company of Shiraz. Materials and Methods: this is a descriptive-analytic and sectional study. At first, by taking letter of recommendation of Islamic Azad university of Marvdasht to health service canters of Oil Company, necessary permissions were taken from clinics of Oil Company. The population form was prepared from all wives of Oil company staff in Shiraz and sampling was done randomly. 500 subjects were obtained by the formula. In order to measure the weight, digital scale (with error of 100 g) was used and its validity was confirmed. The weight and height were measured by a skilful person without shoes with light and thin cloths and body mass index was calculated. In order to analyze statistical data, SPSS version 21 was used in addition to Chi-square test, Fisher Exacttest and ANOVA. Results and Conclusion: results showed that among 500 subjects under study, the weight of 30% (154 persons) was normal, the weight of 3% (15 persons) was low, 34.8% of them had overweight (174 persons), 14% (75) had obesity type 1, 13.2% had obesity type 2 (66 persons), 4.2% had obesity type 3 (21persons). Mean age was 47.3 ±8.1, mean weight was ± 72 ±5.6 and mean height was 159.3±5.6. 425 of women were housewives and others had jobs. Also among the husbands of the women under study, 204 husbands were retired (40.8%) and 296 husbands (59.2%) were still working in Oil company. the salary of 376 persons (75.2%) was monthly higher than three million tomans and others were paid approximately three million tomans per month. 249 persons (49.8%) were walking continuously as an exercise, 201 persons (40.2%) did no exercises and others did trivial activities such as aerobic and swimming (10%).